Educational Services for Children with Autism Spectrum Disorder (ASD) in Autism Special School - Kiki Rezkiani; Imas Diana (CV. Pusdikra Mitra Jaya, 2023)
The right educational services will help children with autism spectrum disorder (ASD) children to optimize their abilities. The purpose of this study was to analyze educational services for ASD children provided by a special ASD school in Bandung. This research uses qualitative methods in the form of case studies. Research instruments using interviews, observation, and documentation. The validity of the data is using the triangulation method. This study found that ASD special schools have provided optimal educational services according to the subjects' needs. The educational services provided follow the principles of teaching and learning, curriculum, approaches and methods, teaching and learning tools, and evaluation. Choosing the right educational service will help subjects optimally increase their potential. The implication of this research is program recommendations for teachers and parents in the continuation of the program that has been carried out to get optimal results for the subject.